2022
DOI: 10.3389/fcvm.2022.805505
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Takayasu Arteritis and Vascular Ehlers–Danlos Syndrome: A Case Report

Abstract: Takayasu arteritis (TAK) is a rare primary systemic inflammatory vasculopathy. It is classified as a large-vessel vasculitis and is known to cause inflammatory aneurysms and vascular stenosis. Vascular Ehlers–Danlos syndrome (vEDS) is an autosomal dominant condition known to cause multiple aneurysms and arterial dissection at a young age owing to a mutation in the gene for type III collagen, COL3A1. Here, we present a case of TAK associated with vEDS with the development of multi-organ infarction of the brain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…COL5A1 or COL5A2 genes, which normally code for collagen chains α1(V) and α2 (V), are mutated and an abnormal coding results in structurally and functionally defective type V collagen [ 16 ]. Hashimoto et al [ 17 ] reported a case of TA associated with EDS, causing multiple aneurysms and arterial dissection at a young age owing to a mutation in the gene for type III collagen, COL3A1, without any ocular signs or symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…COL5A1 or COL5A2 genes, which normally code for collagen chains α1(V) and α2 (V), are mutated and an abnormal coding results in structurally and functionally defective type V collagen [ 16 ]. Hashimoto et al [ 17 ] reported a case of TA associated with EDS, causing multiple aneurysms and arterial dissection at a young age owing to a mutation in the gene for type III collagen, COL3A1, without any ocular signs or symptoms.…”
Section: Discussionmentioning
confidence: 99%